The consistency of UK pension fund trustee decision-making - Clark, G; Caerlewy-Smith, E; Marshall, J (Cambridge University Press, 2007)
An important research programme in the social sciences concerns the theory and practice of individual decision-making under conditions of risk and uncertainty. At the same time, it is apparent that western governments increasingly rely upon individuals to plan and maintain savings programmes to meet their income aspirations: the long-term retirement income of those outside of the welfare state depends a great deal on the competence and consistency of individual decision-making. In this paper, we use a set of problems requiring the same techniques of judgement to test the consistency of trustee decision-making. Respondents were a group of trustees drawn from select UK defined benefit pension plans compared with a larger group of Oxford undergraduates. It was found that many respondents were inconsistent across related problems requiring the application of probabilistic judgement. It is also shown that trustees were more consistent than many undergraduates and it appears that trustee education and professional qualifications can make a positive difference to consistent decision-making. A more challenging test that depends upon understanding the relationship between demographic ageing, immigration, and the financing of pay-as-you-go social security suggests that substantive knowledge and consistency of judgement are crucial components of expertise. Implications are drawn for the trustee institution and the wider debate over the role and significance of individual decision-making with respect to income aspirations.